The Role of The Direct Historical Approach in North American Ethnoarchaeology: A Northern Perspective. (2nd January 2017) - Deal, Michael
ABSTRACT: The direct historical approach, which draws cultural links between the historic and prehistoric past at specific locations, has a longstanding, and at times controversial, history in archaeological interpretation. Evidence from this and related approaches, such as ethnohistorical reconstruction, historical linguistics, oral tradition, and native folklore, is widely employed today by North American archaeologists. It is also a commonly held idea that ethnoarchaeological models are most valuable when they can be linked through historical documentation to past cultures in the same region. The direct historical approach, where applicable, can provide a reliable form of analogical reasoning in ethnoarchaeological studies. However, the historical record is not equal in each region, and researchers must take into account the level of cultural change due to European contact. This paper uses selected examples from northern North America to revisit the role of the direct historical approach in ethnoarchaeological research.